The Influence of Fintech Literacy and Technology Acceptance on the Intention and Usage Behavior of QRIS in Daily Transactions - Ahmad Rexy Hidayat; Kartini (Journal Development Manecos, 2026)
This study aims to analyze the effects of performance expectancy, effort expectancy, social influence, facilitating conditions, and fintech literacy on behavioral intention and actual usage behavior of QRIS in daily transactions. A quantitative approach was employed using a survey method, with data collected from 209 respondents who have used QRIS. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that social influence and fintech literacy have a positive and significant effect on behavioral intention, while performance expectancy, effort expectancy, and facilitating conditions do not have a significant effect. Furthermore, behavioral intention is found to have a positive and significant effect on actual usage behavior. These findings suggest that social factors and users’ cognitive capabilities, particularly fintech literacy, play a more dominant role than traditional technological factors in influencing QRIS adoption. This study contributes to the literature by extending the UTAUT with fintech literacy, highlighting the importance of user capability in understanding digital financial technology adoption. The results also provide practical implications for policymakers and stakeholders to enhance QRIS adoption through digital literacy and financial education initiatives.